Oscar Peterson’s piano prostheses: Strategies of performance and publicity in the post-stroke phase of his career - Lubet, Alex (Jazz Research Journal, 2015)
In 1993, Oscar Peterson had a stroke that rendered him in essence a right-hand-only pianist. He resumed performing from 1994 until shortly before his death in 2007. The stroke. This paper examines how Peterson and his handlers employed “piano prostheses” to assist him. Two categories of prosthetic, analogous to uses of actual artificial limbs, are observed: 1) “performance;” band mates provide accompanimental support different from his pre-stroke groups 2) “cosmetic,” a non-disabled appearance is attempted, mostly by record annotators, by denying/minimizing the stroke’s impact. Peterson appeared ambivalent or vacillating in his attitude toward his disability, sometimes but not always relying on sidemen for extra assistance, and expressing highly varying degrees of openness in his public statements about his limitations. By contrast, his record annotators uniformly ignored or minimized the stroke’s impact. As a disabled public figure, Peterson’s situation is compared to that of Franklin Delano Roosevelt.